Sympathovagal balance analysis in idiopathic postural orthostatictachycardia syndrome - Russo, V.; De Crescenzo, I.; Ammendola, et al., E. (Acta Biomedica Atenei Parmensis, 2007)
The idiopathic postural tachycardia syndrome (POTS) is a complex disorder characterized by chronic orthostatic symptoms and an increase in heart rate within 10 minutes of standing on upright posture, without significant orthostatic hypotension.We describe a case of a 36 year-old patient with POTS, diagnosed by head-up tilt testing. Power spectral analysis of heart rate variability (HRV), performed during the tilt test, revealed the ratio of low and high frequency powers (LF/HF) that increased with the onset of orthostatic intolerance. The increase in LF/HF power ratio may represent sympathetic beta-receptors hyperactivity. Atenolol alleviated his clinical symptoms.